PERAN PENYIDIK DALAM PENEGAKAN HUKUM PEMBELAAN TERPAKSA (NOODWEER) DIHUBUNGKAN DENGAN PASAL 49 (1) KUHP PADA PERKARA KEPOLISIAN POLRESTA SERANG KOTA - Tommy Hidayat; Haidan Angga Kusumah (INTELIGENSIA MEDIA, 2024)
This research aims to find out how the role of the police in imposing suspect status on crime victims and to find out the elements of protection and the elimination of punishment before police investigators sentence crime victims as suspects. The method used in this research is qualitative method. This research was conducted at Serang City Police Station which is located at Jl. Ahmad Yani No.64, Cipare, Kec. Serang, Serang City, Banten 42117. And at the Serang City District Attorney's Office which is located at Jl. Raya Pandeglang Blok Cipare No.11, RT.1/RW.17, Cipare, Kec. Serang, Serang City, Banten 42117. Data collection techniques in this research are observation, interviews, documentation and literature study. The data analysis technique used in this research is the case method analysis technique and descriptive analytical research typology. The results showed that the police play a role in collecting sufficient evidence to determine the extent of each individual's role in a criminal offense, both as the main perpetrator and as a participant and are responsible for conducting in-depth investigations to prove the involvement of each person in the criminal offense committed. In Muhyani's case, based on the investigation by the prosecutor at the prosecutor's office, it was found that there was an element of noodweer, namely coercion as a form of self- defense by protecting his property and protecting his soul. Therefore, Muhyani was not convicted